N-isopropylbenzylamine, a methamphetamine mimics, produces toxicity via increasing nitric oxide in vitro. (October 2022) - Xu, Peng; Li, Haijie; Qiu, Qiyang; Xiao, Xiao; Qiu, Yi; Li, Xiangyu; Wang, Youmei; Zhou, Wenhua; Shen, Haowei; Cui, Wei
Abstract: N-isopropylbenzylamine, an isomer of methamphetamine, has been used to adulterate methamphetamine, and distributed as fake "Ice" methamphetamine by illicit manufacturers, leading to a world problem of N-isopropylbenzylamine exposure. Though it is unclear whether N-isopropylbenzylamine has addictive potential like methamphetamine, N-isopropylbenzylamine users reported side effects such as headaches and confusion. However, the pharmacological targets and cytotoxicity of this chemical remained unknown. In this study, in vitro toxicity of N-isopropylbenzylamine and its toxicity-related targets were investigated in SN4741, SH-SY5Y or PC12 cell lines that model neurons. The cell viability was analyzed by using MTT assay after incubation with N-isopropylbenzylamine for 24 h in cells. N-isopropylbenzylamine caused cell death with IC50 values at around 1–3 mM in these cell lines. N-isopropylbenzylamine time- and concentration-dependently facilitated the expression of neuronal nitric oxide synthase (nNOS), and increased intracellular nitric oxide (NO) in SN4741 cells. Furthermore, 7-nitroindazole, a specific inhibitor of nNOS, significantly prevented N-isopropylbenzylamine-induced toxicity in vitro . These results suggested that N-isopropylbenzylamine-induced toxicity is at least partially related to the increased intracellular NO levels and the activated nNOS. Considering the circumstances that N-isopropylbenzylamine was used to adulterate and mimic methamphetamine, and the side effects associated with N-isopropylbenzylamine in abusers, our findings sounded an alarm for abuser and warn the dangerousness of N-isopropylbenzylamine for public health.